2010
DOI: 10.1007/s10995-010-0724-2
|View full text |Cite
|
Sign up to set email alerts
|

Misreport of Gestational Weight Gain (GWG) in Birth Certificate Data

Abstract: Birth certificates are potentially a valuable source of information for studying gestational weight gain (GWG) during pregnancy, particularly important given new Institute of Medicine (IOM) guidelines. We examined factors associated with the accuracy of maternal GWG self-report by linking the gold standard obstetric electronic medical record (EMR) of women from a large urban practice to state birth certificates. Primary outcomes included maternal under-reporting of GWG (>10 lbs below the EMR), accurate reporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 19 publications
2
23
0
Order By: Relevance
“…These factors could lead to important differences in the accuracy of maternal weight data on birth certificates. Nevertheless, our study suggests that the degree of error is similar to what we and others previously observed among singletons (Bodnar et al 2014) (Vinikoor et al 2010; Park et al 2011; Wright et al 2012). …”
Section: Discussionsupporting
confidence: 91%
“…These factors could lead to important differences in the accuracy of maternal weight data on birth certificates. Nevertheless, our study suggests that the degree of error is similar to what we and others previously observed among singletons (Bodnar et al 2014) (Vinikoor et al 2010; Park et al 2011; Wright et al 2012). …”
Section: Discussionsupporting
confidence: 91%
“…52 In a smaller, clinic-based study, Wright et al found that gestational weight gain recorded in birth certificates was within 4.5 kg for 48% of women, whereas 52% had weight gain either over-or under-reported by at least 4.5 kg. 53 For the misreporting of BMI to have accounted for the findings of this study, a systematic relationship between maternal misreporting and the odds of child ID would be needed. Rothman describes how non-differential misclassification can result in a bias away from the null if the exposure variable is continuous (like BMI).…”
Section: Discussionmentioning
confidence: 99%
“…1 Limitation in intellectual ability corresponds to an intelligence quotient (IQ) of <70, described as mild (IQ 55-70), moderate (IQ [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55], or severe to profound (IQ of <40). 2 The prevalence of ID in the general population is estimated to be approximately 1%, and among those with ID 85% are characterised as having mild ID.…”
Section: Introductionmentioning
confidence: 99%
“…A limitation is that maternal pre-pregnancy weight and total GWG were self-reported, which might have led to misclassification. However, studies have shown that recall of pre-pregnancy BMI and GWG is reproducible and valid (46) and underreporting of GWG, which tends to be more frequent than over-reporting, would most likely bias estimates toward the null (47, 48). We were not able to disentangle the effects of 2 nd and 3 rd trimester GWG, as we had no data on maternal weight at the end of the 2 nd trimester of pregnancy.…”
Section: Commentmentioning
confidence: 99%